KOMPETENSI PROFESI KONSELOR UNTUK MENDUKUNG PELAKSANAAN LAYANAN KONSELING KELOMPOK - Ardiani febriana; Yansi Larbona; Happy Karina Marjo (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
Guidance and counseling is a professional service in educational units carried out by professional educators, namely counselors or guidance and counseling teachers who have competency standards that must be met for effective and efficient services. Regulation of the Minister of National Education no. 27 of 2008 concerning Qualification Standards and Counselor Competencies has explained in full. Group counseling is a counseling service provided to several counselees in a group setting by utilizing group dynamics to learn from each other's experiences. This study uses a literature review research method using 3 keywords namely Counselor Competensies; Counselor School; Group Counseling. The results of the literature study obtained 4 suitable articles.